Inheritance Law System: Considering the Pluralism of Customary Law in Indonesia - Sonny Dewi Judiasih; Efa Laela Fakhriah (Faculty of Law, Universitas Padjadjaran, 2018)
AbstractCustomary inheritance law in Indonesia consists of unique and specific patterns that describe the values of traditional Indonesian society that are based on collective and communal culture. There are three types of customary inheritance system: patrilineal, matrilineal, and parental. Every system has a uniqueness that makes it different with others. These differences often cause disputes and problems. The problems are related especially to the status of men and women in relation to patriarchal and matriarchal systems. Settlement of inheritance is done through discussion, approval, or legal remedies. Judges' decisions indicate that there is a renewal on the customary inheritance system in which men and women have equal opportunities to become inheritors of their parents. Abstrak Hukum waris adat di Indonesia terdiri dari pola unik dan spesifik yang menggambarkan nilai-nilai masyarakat tradisional Indonesia berdasarkan budaya kolektif dan komunal. Terdapat tiga macam sistem waris adat: patrilineal, matrilineal, dan parental. Setiap sistem memiliki perbedaan dan seringkali perbedaan tersebut menimbulkan sengketa dan masalah, terutama terkait dengan status laki-laki dan perempuan dalam hubungan sistem patriaki dan matriaki. Penyelesaian sengekta waris dilakukan melalui diskusi, persetujuan, atau upaya hukum. Putusan hakim mengindikasikan terdapat pembaharuan sistem waris adat di mana laki-laki dan perempuan memiliki kesempatan yang sama untuk menjadi ahli waris orang tua mereka. DOI: https://doi.org/10.22304/pjih.v5n2.a6